Analisis Coolant Dromus Beserta Variasi Coolant dari Minyak Kelapa dan Jagung terhadap Kekasaran Permukaan Material Baja ST-60 pada Pembubutan Konvensional - Rony Irawan; Nurhadi Nurhadi; Fendy Kussuma (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Product quality is affected by the conventional turning process that requires coolant to maintain surface smoothness and reduce tool wear. Vegetable oils such as coconut, corn, and palm oil are environmentally friendly alternatives to chemical coolants (dromus). This study tested the effect of vegetable coolants on the surface of ST 60 steel using an experimental method with variations in a mixture of oil, water, and liquid soap. Turning was carried out at a depth of 0.5 mm, a rotation speed of 1035 rpm, and a cutting speed of 65 mm/min. The results showed that the lowest roughness was in variation 7 (80% corn oil + 10% water + 10% liquid soap) with an initial roughness value of 2.438